Learning and intelligent optimization : 11th International Conference, LION 11, Nizhny Novgorod, Russia, June 19-21, 2017, Revised selected papers /: 11th International Conference, LION 11, Nizhny Novgorod, Russia, June 19-21, 2017, Revised selected papers. (2017) - Unknown
No abstract available